Tsunami simulation due to seaquake at Manila Trench and Sulu Trench - Mardi N.H.; Malek M.A.; Liew M.S. (Springer Netherlands, 2023)
computer simulation; earthquake rupture; environmental disturbance; numerical model; seismic source; tsunami; wave height; East Malaysia; Malaysia; Manila Trench; Pacific Ocean; Sabah; Sarawak; South China Sea; Sulu Sea; Sulu Trench; West Malaysia